Changes in non-motor symptoms in patients with Parkinson's disease following COVID-19 pandemic restrictions: A systematic review - Mameli, Francesca; Zirone, Eleonora; Capetti, Benedetta; Mellace, Denise; Ferrucci, Roberta; Franco, Giulia; Di Fonzo, Alessio; Barbieri, Sergio; Ruggiero, Fabiana (Frontiers in Psychology, 2022)
This review discussed the effects of the impact of the Coronavirus Disease 2019 (COVID-19) pandemic on the psychological wellbeing of people with Parkinson's disease (PD) focusing specifically on depressive symptoms, anxiety levels, sleep, and quality of life (QoL). Together with motor symptoms, psychological symptoms are common and disabling conditions in the clinical course of PD becoming a relevant topic as a result of the lockdown measure due to alter their everyday life. We searched on PubMed online electronic databases for English articles published between January 2020 and 31 December 2021. Twenty-eight relevant studies were found and included in the review. Heterogeneous data emerged from the topics analyzed. Overall, data from depression studies showed significant depressive symptoms if the patient was analyzed longitudinally or vs. a control group consisting in healthy subjects, while these differences become minimal when the control group is a family member. Differently, in most of the studies reviewed there is no evidence of a statistically significant impact on anxiety disorders, nor on the quality of sleep. Conversely, PD patients showed a statistically significant negative impact of QoL compared with control groups or other neurological conditions. Although these findings must be interpreted carefully in the light of the studies' limitations, both in methodology and design, collectively our review showed that COVID-19 pandemic has had negative effects on the mental health of people with PD, due to disruption of healthcare services, loss of usual activities and supports and reduction in physical activity.